HORISON PRAGMATIC PLURALISM SEBAGAI PARADIGMA (BERBAHASA) PENUMBUH INKLUSIVITAS BERAGAMA: ANALISIS BAHASA KEAGAMAAN DALAM FILM NEGERI TANPA TELINGA - Muhammad War’i (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2015)
This paper aims to open religious understanding that concerns not only on startling speech but also behavior aspects. Movie entitled “Negeri Tanpa Telinga” movie directs towards the deconstruction of language describing the use of religious language which is often just as a feigned imaging. Language is not solely a reflection of the attitude determined grammatically. Language understanding should be plural so it can guide someone towards pragmatic pluralism horizon. This view will give more impact to someone’s life inclusiveness including in terms of religion.